S-S bridges of cathepsin B and H from bovine spleen: a basis for cathepsin B model building and possible functional implications for discrimination between exo- and endopeptidase activities among cathepsins B, H and L - Baudys, M; Meloun, B; Gan-Erdene, T; Fusek, M; Mares, M; Kostka, V; Pohl, J; Blake, C C (Biomedica biochimica acta, 1991)
Bovine spleen cathepsin B contains 7 disulfide bridges. Using different chemical and enzymatic cleavage methods we isolated fragments representing the individual disulfides: Cys14-Cys43, Cys26-Cys71, Cys62-Cys128, Cys63-Cys67, Cys100-Cys132, Cys108-Cys119, and Cys148-Cys252. A similar line of approach was applied to determine the S-S bridges of bovine spleen cathepsin H: Cys23-Cys66, Cys57-Cys99, Cys157-Cys207, and Cys212-Cys5A, where Cys5A is located in the propart portion of the procathepsin H chain. On the basis of the knowledge of the S-S bridges of cathepsin B a novel sequence alignment of papain and cathepsin B has been proposed. This enabled us to construct a reasonable 3D-model of cathepsin B and propose the region (a 18 residue insertion between Glu89 and Gly90 of papain) responsible for the carboxypeptidase activity of cathepsin B functioning as a "closure". A similar approach was applied to explain the aminopeptidase activity of cathepsin H. A general model of steric regulation of accessibility of the preformed "endopeptidase-like" binding cleft by distant parts of the polypeptide chain of the proteinases discussed is proposed as a factor determining the mode of binding and thus cleavage of polypeptide substrates.
Keywords: kathepsin L; Cattle; exopeptidasy; Sequence Homology, Nucleic Acid; Endopeptidases; vazebná místa; kathepsin B; slezina; cysteinové endopeptidasy; Peptide Hydrolases; skot; cystein; molekulární sekvence - údaje; Amino Acid Sequence; sekvenční homologie nukleových kyselin; Disulfides; Cathepsin L; molekulární modely; Cysteine; Cathepsins; Spleen; Models, Molecular; Binding Sites; kathepsiny; Cathepsin H; Animals; konformace proteinů; zvířata; Cysteine Endopeptidases; kathepsin H; endopeptidasy; sekvence aminokyselin; Exopeptidases; Molecular Sequence Data; Cathepsin B; Protein Conformation; disulfidy; proteasy